2021
DOI: 10.3390/atmos12060688
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Atmosphere-Ocean Coupling on the Structure and Intensity of Tropical Cyclone Bejisa in the Southwest Indian Ocean

Abstract: A set of numerical simulations is relied upon to evaluate the impact of air-sea interactions on the behaviour of tropical cyclone (TC) Bejisa (2014), using various configurations of the coupled ocean-atmosphere numerical system Meso-NH-NEMO. Uncoupled (SST constant) as well as 1D (use of a 1D ocean mixed layer) and 3D (full 3D ocean) coupled experiments are conducted to evaluate the impact of the oceanic response and dynamic processes, with emphasis on the simulated structure and intensity of TC Bejisa. Althou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 51 publications
1
5
0
Order By: Relevance
“…As expected in the South hemisphere, the upwelling in the CPL runs is located on the left side of the TC track in the direction of propagation (Bielli et al, 2021;Pianezze et al, 2018;Price, 1981), so on the East side of Gelena (Figures 10b-10d). In this zone, the thermocline, which corresponds to the thermal transition zone between the deep cold waters and the warmer well mixed surface waters initially at about 50 m depth, is pushed toward the surface by the upwelling.…”
Section: Simulations Of Tc Gelenasupporting
confidence: 74%
See 1 more Smart Citation
“…As expected in the South hemisphere, the upwelling in the CPL runs is located on the left side of the TC track in the direction of propagation (Bielli et al, 2021;Pianezze et al, 2018;Price, 1981), so on the East side of Gelena (Figures 10b-10d). In this zone, the thermocline, which corresponds to the thermal transition zone between the deep cold waters and the warmer well mixed surface waters initially at about 50 m depth, is pushed toward the surface by the upwelling.…”
Section: Simulations Of Tc Gelenasupporting
confidence: 74%
“…The numerical simulation of such a process driven by the explicit advection of the oceanic currents needs a 3D ocean model (Mogensen et al., 2017; Yablonsky & Ginis, 2009). Numerous studies have indeed shown the benefit of modeling the upwelling effect in a 3D ocean model for TC forecasting (Bender et al., 2007; Bielli et al., 2021; Ginis, 2002; Jullien et al., 2014; Mogensen et al., 2017; Yablonsky & Ginis, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…This presents a broad view of the possible changes in the thermal structure of the upper ocean in the aftermath of a TC, which could in turn significantly impact oceanic preconditioning and subsequently affect the intensity of upcoming TCs 57 , 58 . Coupled ocean–atmosphere models improve TC forecasts significantly by incorporating the ocean impact into the model, which is particularly notable in slow-moving TC cases 59 , 60 . Reevaluating the downwelling process in the ocean could also benefit the parameterization of numerical models for TC forecasting.…”
Section: Discussionmentioning
confidence: 99%
“…However, only a small number of cumulus parameterization and cloud microphysics schemes were tested in this study, so there is a need to conduct more sensitivity experiments using diverse kinds of physics parametrization schemes in the future for a more sophisticated forecast performance verification. Besides, various methods to achieve better performances in typhoon forecast have been introduced by lots of studies; increasing the model horizontal resolutions (Buizza, 2010; Davis et al., 2010), improving initial condition (Cha & Wang, 2013; Y. Choi, Cha, & Kim, 2017; Kurihara et al., 1993; Liu & Tan, 2016), using alternative boundary condition (Moon et al., 2018), and reflecting the realistic atmosphere and ocean interactions by using atmospheric‐ocean coupled models (Bielli et al., 2021; Kim et al., 2014; Mogensen et al., 2017; Yesubabu et al., 2020). Therefore, other factors also should be considered and included in future studies with optimal physics combinations to further improve the overall typhoon forecast.…”
Section: Discussionmentioning
confidence: 99%